Ecogeomorphology and human use description of geosites included in the Andalusian geoconservation inventory from the Subbeticas Natural Park and Geopark (Spain) - Menjíbar-Romero, Mario; Martínez-Murillo, Juan Francisco (My University, 2022)
Geoparks are territories characterising by remarkale geodiversity and/or impressive geosites which deserves their preservation as well as the dissemination. This study deals with the description of the ecogeomorphology and past and current human use from remarkable geosites included in the Andalusian Geoconservation Inventory. All of them are located in the Subbéticas Natural Park and Geopark area (Province of Córdoba, in southern Spain). This geopark belongs to the European and World Geopark Network since 2006. The landscape and geology of the Geopark are closely related; ridges are formed of hard limestone; valleys are created in areas underlain by softer argillaceous carbonates and other detrital sediments. The rocks, which range in age from the Jurassic to the Tertiary, were deposited approximately between 200 million years and 25 million years ago. The rocks are rich in fossils and are noted for their Mesozoic ammonites. The Geopark is internationally recognised as one of the most significant areas for the study of the evolution of this group of fossils. In total, there 16-geosites within the geopark besides four more in the surroundings. The geosites are mainly related to karstic processes and landforms, but also there are others related to geological structures and fossils. This study is focussed in sharing the results of their description from a holistic point of view considering ecogeomorphology and human uses in order to enrich the current information from all of them and improving their dissemination among the geopark visitors.
Keywords: Parque Natural Sierras Subbéticas (Córdoba) - Conservacíón; Geopark; Geosite; Subbéticas; Natural Park